Organizational aspects of an experimental program for physical education with a strengthened course in professional and applied physical training of future electrical engineers in the railway sector - Єфремова, Анжеліка; Шестерова, Людмила (Slobozhanskyi Herald of Science and Sport, 2017)
Anzhelika Yefremova, Liudmyla Shesterova Purpose: to develop an optimized program for physical education with a strengthened course in professional and applied physical training (PAPT) for students of railway universities. Material & Methods: analysis and generalization of scientific sources and program-normative documentation on physical education of the higher educational institution of railway transport, survey. Results: the results of the survey of railroad specialists are given. Pilot studies have determined the nature and conditions of professional activity of electrical engineers of railway transport. The experimental program on physical education with the strengthened course of the PAPT of students of railway universities was developed and theoretically justified. Conclusion: structure of the experimental program on physical education with the strengthened course of the PAPT included a theoretical section (8 hours), methodical and practical exercises (6 hours), a practical section (114 hours) and a control section (12 hours). The program focuses on improving professionally important physical and psycho-physiological qualities and functions, psychomotor skills and physical performance. The basis of the practical section was the physical exercises from different sections of the current basic curriculum.